PENGARUH PENGGUNAAN MEDIA BONEKA TANGAN TERHADAP PENAMPILAN MENYIMAK CERITA PADA ANAK USIA DINI DI R. A AL – WARDAH PANDEGLANG - Enong Humaeroh; Uyu Mu’awwanah; Wulan Fauzia (JIP: Jurnal Ilmu Pendidikan, 2026)
The objectives of this study were: 1) To determine whether hand puppets can influence story listening skills in early childhood education at RA Al-Wardah. 2) To determine whether the use of hand puppets can improve children's ability to listen to stories. This quantitative study employed an experimental method with a pre-experimental design. Data collection used a pretest-posttest. The subjects in this study were Group B at RA Al-Wardah Pandeglang. Class B4 served as the experimental class, with no comparison group, pretest-posttest. Data analysis used descriptive analysis, inferential analysis, and normality testing (Shapiro-Wilk test). The results of this study indicate that, based on SPSS version 31, the hypothesis test using a paired sample t-test yielded a t-value of 0.71, with a significance value of 0.000 <0.05. Therefore, based on the test criteria, it can be concluded that Ha is accepted and Ho is rejected, indicating that educational puzzle games influence children's cognitive abilities. This is further supported by the results of the paired sample t-test, which showed a Cohen's d value of 3.58, categorized as having a very large influence.